Predictive factors for non-response to intravitreal ranibizumab treatment in age-related macular degeneration - Suzuki, Misa (BMJ Publishing Group, 2014)
BACKGROUND/AIMS: To study the initial characteristics and response to intravitreal ranibizumab (IVR) treatment of age-related macular degeneration (AMD). METHODS: We reviewed the clinical records of 141 eyes in 141 AMD patients who received monthly IVR for 3 months and thereafter pro re nata (PRN) injections for 9 months as the first treatment for AMD. Patients whose best corrected visual acuity (BCVA) worsened at month 12, and those with increased exudative fundus findings after IVR or an increased central retinal thickness of more than 100 μm at month 12, were considered to be non-responders as judged by BCVA and fundus findings, respectively. Non-responders’ initial characteristics were analysed using logistic regression models. RESULTS: 14.9% of eyes were non-responders as judged by BCVA, and 17.0% were non-responders as judged by fundus findings. Initial fibrovascular pigment epithelial detachment (PED) (OR 22.9, 95% CI 2.61 to 201) and serous PED (OR 4.12, 95% CI 1.08 to 15.8) were associated with non-response as judged by BCVA. Initial fibrovascular PED (OR 33.5, 95% CI 2.95 to 381) and type 1 choroidal neovascularization (OR 6.46, 95% CI 1.39 to 30.0) were associated with non-response, as judged by fundus findings. CONCLUSIONS: Although most AMD responded to IVR, non-responders had initial clinical characteristics that might be informative for managing their treatment.